Efek Rekrutmen Dan Penempatan Terhadap Kinerja Karyawan Dengan Pengembangan Karir Sebagai Variabel Intervening Pada PT SAI Apparel Industries - Aulia Syifa Salsabila; Kasmari Kasmari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the effect of recruitment and placement on employee performance through employee career development at PT Sai Apparel Industries. This research used a quantitative approach with a sample of 90 respondents. The sampling technique is Accidental Sampling with calculations resulting from the Solvin formula. The data processing technique in this research uses SmartPLS 3 software. The results of this research can be concluded that recruitment does not have a significant effect on the performance of PT Sai Apparel Industries employees, Recruitment has a positive and significant effect on the career development of PT Sai Apparel Industries employees, Placement has a positive and significant effect on the performance of PT Sai Apparel Industries employees, Placements have a positive and significant effect on the career development of PT Sai Apparel Industries employees, Career Development has a positive and significant effect on the performance of PT Sai Apparel Industries employees, Recruitment influences employee performance through employee development at PT Sai Apparel Industries, Placement does not have a significant effect on employee performance if it is through PT Sai Apparel Industries Employee Career Development. Keywords: Recruitment, Placement, Employee Performance, Career Development